Pharmacological inhibition of mitochondrial fission attenuates oxidative stress-induced damage of retinal pigmented epithelial cells - Tomohiro Yako; Maho Nakamura; Shinsuke Nakamura; Hideaki Hara; Masamitsu Shimazawa (Elsevier, 2021)
Mitochondria maintain their function by the process of mitochondrial dynamics, which involves repeated fusion and fission. It is thought that the failure of mitochondrial dynamics, especially excessive fission, is related to the progression of several diseases. A previous study demonstrated that mitochondrial fragmentation occurs in the retinal pigmented epithelial (RPE) cells of patients with non-exudative age-related macular degeneration (AMD). We predicted that the suppression of mitochondrial fragmentation offers a novel therapeutic strategy for non-exudative AMD. We investigated whether the inhibition of mitochondrial fission was effective against the oxidative stress-induced damage of ARPE-19 cells. The treatment of ARPE-19 cells with H2O2 caused mitochondrial fragmentation, but treatment with mitochondrial division inhibitor 1 (Mdivi-1) suppressed fragmentation. Additionally, Mdivi-1 protected ARPE-19 cells against H2O2-induced damage, and suppressed the release of cytochrome c from the mitochondria. Mitochondrial function was evaluated by staining with JC-1 and measuring the production of reactive oxygen species (ROS), which revealed that mitochondrial function improved in the Mdivi-1-treated group. These findings indicated that the inhibition of mitochondrial fission would be a novel therapeutic target for non-exudative AMD.